Phenological strategies of an evergreen tree in the Caatinga. - Fernanda Moura Fonseca Lucas; Kyvia Pontes Teixeira das Chagas; Ageu da Silva Monteiro Freire; Vivian Raquel Bezerra de Sousa; Fábio de Almeida Vieira (PLoS ONE)
Seasonally Dry Tropical Forests (SDTF) account for 40% of global tropical forests, with the Caatinga standing out as the largest continuous formation of this type. However, the region faces severe threats, such as deforestation and desertification, which require urgent conservation efforts. In this context, understanding the adaptive strategies of native species becomes essential to support management actions. This study aims to identify the phenological strategies of Sarcomphalus joazeiro (Mart.), a species of high ecological, cultural, and economic importance in the region. Over two years, intrapopulation monitoring of vegetative and reproductive phenophases was conducted in a forest fragment in Rio Grande do Norte, Brazil, evaluating phenophase seasonality, reproductive synchrony, correlation with meteorological variables (precipitation, relative humidity, and air temperature), and fruit and seed biometrics. The results revealed that the flowering and fruiting of S. joazeiro are annual, synchronized, and occur during the dry season, highlighting an adaptive reproductive strategy and providing an important food source for the fauna. The species exhibited a weak correlation between its phenophases and meteorological variables, emphasizing its resistance to adverse climatic conditions. These characteristics make S. joazeiro unique among SDTF trees and underscore its ecological importance and potential for management and degraded area restoration strategies. Phenological studies with other Caatinga species are recommended to deepen understanding of biota-climate interactions and to contribute to effective conservation strategies.